To involve passive students in teaching foreign languages - Sayfutdinova Nilufarkhan Soyibjonovna (Zien Journals, 2022)
This article provides information on working with students with low mastery rates and methods used in the course of teaching foreign languages.
Keywords: foreign language; teacher; teaching methodology; modern innovative technologies